CULTURAL, EDUCATIONAL AND CHARITABLE ACTIVITIES OF THE GREEK-CATHOLIC CHURCH IN EASTERN GALICIA IN THE INTERWAR PERIOD - ZULYAK, Ivan (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The purpose of the study is to analyze the key areas of cultural, educational and charitable activities of the Greek Catholic Church during the period when Eastern Galicia was part of the Polish Republic. The research methodology is based on the principles of historicism, scientificity, objectivity, and systematicity. General scientific (analysis, synthesis, generalization) and special historical (historical-genetic, historical-systemic) methods were used. The scientific novelty lies in the comprehensive study and analysis of the stated topic, which makes it possible to clarify the main directions of cultural, educational, charitable activities of the Greek-Catholic clergy of Eastern Galicia in the interwar period. Conclusions. The clergy of the GCC actively participated in the organization of cultural and educational processes, organized support measures for the needy population in Eastern Galicia. A powerful educational work was carried out by the congregation of the Order of St. Basil the Great (OSGV) and the Sisters Servants of the Immaculate Virgin Mary (SSIM), who took care of the work of «burial grounds», schools and generally helped parishioners. The priests used their own funds to establish schools with Ukrainian as the language of instruction, provide financial assistance to talented children, and participate in the work of the «Ridna Shkola» and «Prosvita» societies. Such institutions were popular among Ukrainians who wanted to preserve their national identity. The clergy traditionally created religious brotherhoods in communities that had different themes. Each pastor reported on their functioning and membership at deanery councils. Metropolitan A. Sheptytsky initiated the opening of the Ukrainian National Museum in Lviv, which in the interwar period became a center for the preservation of unique cultural artifacts, served as a cultural center, and was a symbol of the preservation of Ukrainian national identity. The article shows the participation of the Metropolitan and clergy of the GCC in the context of the Church's implementation of social protection measures for Ukrainians. The forms and mechanisms of the Church's charitable work are identified. The content of the work of the «Diocesan Help» society, the Ukrainian Committee for the Unemployed and the Poor, and the Metropolitan Andrey Sheptytsky Orphanage is highlighted. A. Sheptytsky's charitable activity was a significant factor in the existence of various formats of Ukrainian organizations and served as a worthy example for the clergy and believers.